Board Reputation and Financial Reporting Quality - SEGAL, Dan (Institutional Knowledge at Singapore Management University, 2011)
This study uses a new measure of board reputation that is based on the market value of other companies on which board members serve, and examines whether board reputation has a causal effect on monitoring as reflected in financial statement reporting quality. A negative causal effect is expected if reputable directors are ineffective monitors because they are too busy or they choose to cater to management, whereas a positive causal effect is expected if reputable directors are more experienced and subject to significant reputation penalties in the case of a financial reporting failure. An alternative explanation is that reputation does not affect financial reporting quality, but rather is a characteristic of the market for directorship, where the equilibrium relation between reputation and financial reporting quality is determined by the demand for and supply of reputable directors. Our results suggest that financial reporting quality is not an important determinant of the market for directorship. Rather, we document that reputation has a positive causal effect on monitoring and results in higher quality financial reporting.